STRATEGI PEMBANGUNAN EKONOMI SYARIAH PESANTREN MELALUI KOLABORASI KEMENTERIAN AGAMA DAN DINAS PENDIDIKAN DAYAH - Amir Hasan (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
Islamic boarding schools are traditional educational institutions and have their own characteristics, namely independence. Independence is created in several programs according to the needs of Islamic boarding schools and empowerment of potential through the Islamic Boarding School Independence Program. The purpose of writing this study is to formulate a strategy using SWOT and AHP analysis to build the independence of Islamic boarding schools in Aceh Province by collaborating regional potential and the conditions of Islamic boarding schools in Aceh Province. This study was conducted with a qualitative approach, and used SWOT and AHP analysis to formulate priority activities that can be carried out. Results 1) development of Islamic boarding school independence can be conducted by using the strength-opportunity strategy, namely optimizing potential and strength to increase the achievement of opportunities in developing Islamic boarding school independence, 2) strategies obtained by using SWOT analysis are a) making linear Islamic boarding school independence regulations, b) forming a communication forum, c) synergistic planning, d) synergistic human resources, e) mutually supportive budgets and e) program synchronization, 3) the results of the AHP analysis for priority activities for developing Islamic boarding school independence are a) regulation as the first priority activity is carried out with the regulation drafting process activity, b) synchronization is carried out using the priority activity of reviewing legal certainty, c) planning is carried out with the priority activity of making commitments, d) human resources are carried out with the priority activity of selecting, e) communication forums are carried out with the priority activity of involving the community and f) budgets are carried out with the priority activity of determining the scale of needs. Conclusion: development of Islamic boarding school independence in Aceh Province can be realized with collaboration between the Regional Office of the Ministry of Religion of Aceh Province and the Dayah Education Office to synergize.